Wizualizacja wyników analizy danych o preferencjach z wykorzystaniem metod dekompozycyjnych - Bąk, Andrzej (Visualization of Preferences Data Results with the Use of Decompositional Methods, 2009)
The main goal of the paper is to identify the possibilities of visualization of results of the preferences data analysis with the use of decompositional methods, especially conjoint analysis and discrete choice models. As a software tool, some packages and own functions of the CRAN R were applied. The paper includes decompositional methods characteristics, presentation of chosen CRAN R packages and functions, the examples of visualizations of preferences data analysis results.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s.42-54